The Effect of Bismuth on the Performance of a Single‐Cell Iron–Chromium Redox Flow Battery - Nico Mans; Derik van der Westhuizen; Henning Manfred Krieg (Advanced Energy & Sustainability Research, 2024)
This study examines the need for bismuth as a catalyst for the Cr2+/Cr3+ redox couple in an iron–chrome redox flow battery (ICRFB) using 1) open‐circuit voltage (OCV) periods to understand the impact of bismuth and the mechanism of hydrogen production with and without electrolyte flow, and 2) charge/discharge cycles to evaluate how bismuth influences ICRFB performance. The OCV study finds that the capacity decay in the ICRFB cycling is not solely due to the hydrogen evolution reaction, suggesting an alternative oxidation reaction is involved, likely catalyzed by metallic carbides like bismuth carbide. Both the OCV and the ICRFB confirm that the presence of bismuth negatively influences the battery performance due to increased H2 production. Further research is ongoing to validate the decay mechanism and confirm these results on a larger scale.